2010
DOI: 10.1002/art.27384
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the renin–angiotensin system in the development of vascular damage in a rat model of arthritis: Effect of angiotensin receptor blockers

Abstract: Objective. To explore the involvement of the renin-angiotensin system (RAS) in the development of vascular damage in adjuvant-induced arthritis (AIA) in rats.Methods. Angiotensin II (Ang II; 0.25 or 1.0 mg/kg/day) was infused in control rats and rats with AIA for 21 days, and the impact of systemic inflammation on Ang II-induced hypertension, endothelial dysfunction, and vascular hypertrophy was evaluated. Expression of angiotensin II type 1 receptor (AT 1 R) and angiotensin-converting enzyme (ACE) in the aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 48 publications
7
58
1
2
Order By: Relevance
“…To confirm that the abnormal response of vessels from AIA rats to ACh was not due to decreased response of vascular smooth muscle cells to NO, we demonstrated that the relaxing effect of the NO donor SNP was not impaired in the AIA rats. This result is in accordance with recent study findings in AIA rats (12,14,36) as well as in RA patients (37)(38)(39)(40). Likewise, we verified that the contractile response of vessels from AIA rats to NE was not different from that of control rats.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To confirm that the abnormal response of vessels from AIA rats to ACh was not due to decreased response of vascular smooth muscle cells to NO, we demonstrated that the relaxing effect of the NO donor SNP was not impaired in the AIA rats. This result is in accordance with recent study findings in AIA rats (12,14,36) as well as in RA patients (37)(38)(39)(40). Likewise, we verified that the contractile response of vessels from AIA rats to NE was not different from that of control rats.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we investigated endothelial function in the AIA model, which is commonly accepted as having many histologic and clinical features in common with human RA (31) and which is widely used to predict clinical efficacy of new therapies in RA (32). In accordance with previous studies (12)(13)(14)(15)(16)(33)(34)(35), our data show that endothelial function assessed by the vasodilating response to ACh is impaired in AIA rats. We also demonstrated that endothelial dysfunction correlates with disease activity.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Antiinflammatory effects of ARBs have been demonstrated in various clinical conditions as hypertension, radiation-related delayed inflammation, and inflammatory chronic hepatitis C [20][21][22]. In animal studies performed using ARBs, valsartan decreased inflammatory cell infiltration in bronchoalveolar lavage fluid in asthmatics, and losartan suppressed inflammatory processes in sepsis, and arthritis [23][24][25]. Gemici et al [26] detected antiinflammatory effects of candesartan in an animal model of ischemic reperfusion damage.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated antiinflammatory effects of ARBs. In these studies also including telmisartan, favourable effects of ARBs have been displayed on diabetes mellitus and cardiovascular diseases which possess inflammatory properties [10][11][12][13][14]. ARBs are known to decrease inflammation, and oxidative stress which lead to complications in cardiovascular diseases, and diabetes mellitus [15].…”
Section: Introductionmentioning
confidence: 99%